2004
DOI: 10.4315/0362-028x-67.2.357
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of Yeasts in Dairy Products: A Comparison of Immunological and Genetic Techniques

Abstract: Enzyme-linked immunosorbent assay (ELISA) and PCR techniques have been developed for the detection of spoilage yeast species in dairy products. Polyclonal antibodies against live yeast cells (AY) were raised in rabbits by inoculation of a mixture of 10 yeast species frequently associated with dairy products spoilage. AY antibodies were used for the development of two ELISA formats (indirect and double-antibody sandwich ELISA) for the detection of yeast species in milk and yogurt. A PCR assay was also developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Fungi can be particularly troublesome, because they can adapt to the environment of the food and can be difficult to detect on conventional plating media within the standard incubation times. In yogurts, yeasts often grow slowly in conventional laboratory plating methods, but as few as 10 CFU/ml were detectable after 16 h of incubation by PCR amplification of the conserved region of their 18S rRNA (García et al, 2004). Several investigators (Ingham and Ryu, 1995;Vlaemynck, 1994;Beuchat, Nail, Brackett, & Fox, 1990) have made comparisons of a number of alternative yeast and mold detection methods in shredded cheese, hard and soft cheeses, cottage cheese, yogurt, and sour cream, and found that, while results for all of the methods were statistically similar, price, speed, and convenience of use are often overarching considerations when users choose a method.…”
Section: Methods For Detection and Isolationmentioning
confidence: 99%
“…Fungi can be particularly troublesome, because they can adapt to the environment of the food and can be difficult to detect on conventional plating media within the standard incubation times. In yogurts, yeasts often grow slowly in conventional laboratory plating methods, but as few as 10 CFU/ml were detectable after 16 h of incubation by PCR amplification of the conserved region of their 18S rRNA (García et al, 2004). Several investigators (Ingham and Ryu, 1995;Vlaemynck, 1994;Beuchat, Nail, Brackett, & Fox, 1990) have made comparisons of a number of alternative yeast and mold detection methods in shredded cheese, hard and soft cheeses, cottage cheese, yogurt, and sour cream, and found that, while results for all of the methods were statistically similar, price, speed, and convenience of use are often overarching considerations when users choose a method.…”
Section: Methods For Detection and Isolationmentioning
confidence: 99%
“…Reverse transcription (RT)-PCR and real-time RT-PCR assays were developed targeting actin locus for rapid detection and quantification of viable yeasts and molds contaminating yogurt and pasteurized food products [ 31 ]. A PCR assay was developed using the conserved region of 18S rRNA gene for the detection of yeast in dairy products [ 32 ]. For the detection of viable yeast in yogurt samples, this region was used as the genetic marker in developing a PCR and RT-PCR assays as well [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The package is then inflated by gas formed during the fermentation. Yogurt acquires the unpleasant flavor of fermentative yeasts, with gas formation and visible colonies on the surface (Garcia et al., ; Ledenbach & Marshall, ). Geotrichum candidum decreases the amount of diacetyl in cheese (Antinone & Ledford, ; Hang & Woodams, ).…”
Section: Milk and Dairy Productsmentioning
confidence: 99%